A satisfação profissional e a cultura organizacional : uma análise a partir do modelo ASH no Centro Federal de Educação Tecnológica do Rio Grande do Norte - Barbosa, Juliana Rangel (2008)
With the need of the companies in becoming more competitive within the market, it arises an incessant search for selective human potential, with a high level of capacity and low rotativity, which motivation results in production raise, quality optimization and waste reduction. This scenario requires a strategy development which advantages the Human Resources Quality Management. This way, the model of the Human System Audit (HSA), developed by the Spanish researchers Ouijano and Navarro, presents itself as an important tool to diagnosis and evaluation, contemplating the environment where the organization is inserted, its strategies, its organizational design, its processes and its organizational effectiveness. In this sense, the present study has identified the existent relation between the professional satisfaction and the Organizational Culture, based in the model HSA. The research has been a quantitative-descriptive one and has had as population the technical-administrative workers from the Federal Center of Technical Education of Rio Grande do Norte (CEFET RN). The data collection has occurred during May, 2008, by means of the application of a questionnaire in the HSA model. The sample was composed by 167 subjects, distributed among the Five units of the institution. It was used the factorial analysis, with the extraction method of main components and orthogonal rotation varimax, in order to extract the dimensions of the satisfaction and of the organizational culture and the calculation of Cronbach s Alpha coefficient, to evaluate the reliability of these dimensions. The factorial analysis of the satisfaction indicators has identified four factors,, all of them showing significance: gratefulness and relationship , self-realization , stability and security and physical conditions and social benefits . The result of the factorial analysis with the indicators of the organizational culture has extracted four factors and among them, three of them have obtained significance: Personal Satisfaction Style , Competitive-Denial-Power Style and the Conventional-Dependent Style . After identifying the dimensions of the satisfaction and culture found at CEFET-RN, it has been notice the existence or not of relation among them, through the application of Pearson s coefficient. It has been verified that all of the dimensions of the Professional satisfaction are correlated with some dimension of the organizational culture, having in outstand position, with higher intensity, the relation between the culture style of Personal Satisfaction and the satisfaction factor referring to the self-realization